MARKET STRUCTURE AND INCOME OF CARROT FARMING IN SUMBERGONDO VILLAGE, BUMIAJI DISTRICT, BATU CITY - Florentino Davor Syuker; Ana Arifatus Sa'diyah; Ayu Wulandari Priyambodo (Journal of Agricultural Socio-Economics (JASE), 2023)
Carrot is a subtropical vegetable commodity that has the potential to be developed, especially in Indonesia. This study aims to analyze the structure of the carrot commodity market and to analyze the income of carrot farming. The research was conducted in Sumbergonodo Village, Bumi Aji District, Batu City. Market structure analysis was carried out using the Concentration Ratio For Biggest Four (CR4), Hirschman Herfindahl Index, Rosenbluth Index, Gini Coefficient. Meanwhile, income analysis is carried out by analyzing the structure of costs and income. The results show that the market structure that occurs tends to lead to imperfect competition markets because the values of the four analyzes used are CR4 (Concentration Ratio for Biggest Four) Hirschman Herfindahl Index, Rosenbluth Index, and Gini Coefficient, giving an illustration of the value of market share having a dominant value leads to an imperfect competitive market. In addition, the results of the study also show that carrot farming is profitable with a profit value of RP. 14,146,937/ha